Can laboratory-based XAFS compete with XRD and Mössbauer spectroscopy as a tool for quantitative species analysis? Critical evaluation using the example of a natural iron ore - Sebastian Praetz; Christopher Schlesiger; Damian Alexander Motz; Stephen Klimke; Moritz Jahns; Christine Gottschalk; Lena Heinrich; Eva Maria Heppke; Wolfgang Malzer; Franz Renz; Carla Vogt; Birgit Kanngießer (PLoS ONE, 2025)
While X-ray diffraction (XRD) is a commonly used method for quantification analysis using Rietveld refinement and quantitative Mössbauer spectroscopy is sporadically used primarily for iron speciation, laboratory X-ray Absorption Fine Structure Spectroscopy (lab-XAFS) is rarely applied for the quantitative determination of sample compositions. With the recent developments of laboratory-based XAFS spectrometers, this method becomes more interesting for many applications as well as for quantification. The goal of this study is to compare quantitative lab-XAFS via Linear Combination Fitting (LCF) of reference spectra with XRD and Mössbauer spectroscopy. Iron species analysis with the focus on the determination of the mass ratio alpha-iron(III) oxide (α-Fe2O3)/iron(II, III) oxide (Fe3O4) was used as an example. The examinations were performed on synthetic α-Fe2O3/Fe3O4 model mixtures and, predominantly, on a natural iron ore sample mainly consisting of the minerals hematite and magnetite, thus, these two iron oxides. For the iron K-edge lab-XAFS measurements an X-ray tube-based spectrometer using the von Hamos geometry with Highly Annealed Pyrolytic Graphite (HAPG) mosaic crystal optic was used. The capabilities and challenges of each method are discussed. The quantitative model mixtures examinations by lab-XAFS show results and accuracies similar to those obtained by XRD and Mössbauer spectroscopy. However, while the quantitative results for the iron ore investigations by lab-XAFS are in good agreement (deviation of 2 percent points) with the XRD results, the composition determined by Mössbauer spectroscopy differs clearly from the lab-XAFS and XRD results. Furthermore, the Mössbauer spectroscopic examinations hint the presence of an additional iron oxide species affecting the quantification. Besides the still common challenges in identification, differentiation and quantification of different iron oxides, the results show that quantitative lab-XAFS can particularly compete with quantitative XRD when determining the species composition of one element. This makes lab-XAFS particularly well-suited for routine analytics.